2020
DOI: 10.2174/1381612826666200304145224
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Beneficial Effects of the Probiotic Kefir on Vascular Dysfunction in Cardiovascular and Neurodegenerative Diseases

Abstract: : The mechanisms responsible for the cardiovascular and neurodegenerative diseases have been the focus of experimental and clinical studies for decades. Among those studies, the relationship between the gut microbiota and the organs and system tissues, represents the research field that has generated the highest number of publications. Homeostasis of the gut microbiota is important to the host because promotes maturation of the autoimmune system, harmonic integrative functions of the brain and the normal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Furthermore, VJs fortified with LAB feature enhanced flavor and functionally bioactive substances [ 12 ]. Previous studies have confirmed the effects of probiotics on gastrointestinal and allergic diseases, immune modulation [ 13 ], the prevention of various types of cancer [ 14 ], and important roles in maintaining a healthy gut microbiome and prevention of several metabolic and cardiovascular diseases [ 15 ]. Fermented foods and beverages based on vegetable substrates are widely reported for their health-promoting properties, but are insufficiently studied, and their health claims are not supported by reliable scientific evidence [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VJs fortified with LAB feature enhanced flavor and functionally bioactive substances [ 12 ]. Previous studies have confirmed the effects of probiotics on gastrointestinal and allergic diseases, immune modulation [ 13 ], the prevention of various types of cancer [ 14 ], and important roles in maintaining a healthy gut microbiome and prevention of several metabolic and cardiovascular diseases [ 15 ]. Fermented foods and beverages based on vegetable substrates are widely reported for their health-promoting properties, but are insufficiently studied, and their health claims are not supported by reliable scientific evidence [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kefir’s health improving effects have been demonstrated when used in natura 19 , 38 41 , as cell-free fraction 42 45 and as purified peptides 46 50 . However, no previous studies have characterized kefir metabolic composition, or investigated the biological effects of its peptide and cell-free fraction.…”
Section: Discussionmentioning
confidence: 99%
“…As is known, gut homeostasis maintenance by probiotics reinforces the essential function of organs linked to the cardiovascular and metabolism. In contrast, dysbiosis caused by pathogenic and other external factors results in dysfunction of the host’s organs and tissues, resulting in an elevated risk of cardiovascular diseases [ 76 ]. Indeed, the interplay between the intestinal microbiota and the host’s organs and tissues remains an essential factor in understanding the roles of gut microbiota, either probiotics or pathogenic, on cardiovascular diseases ( Table A1 ).…”
Section: Probiotics and Cardiovascular Diseasesmentioning
confidence: 99%